Development of School Management Information System and Learning Management System at RA-Al Hida - Hapsari Widayani; Rudi Bratamanggala (Greenation International Journal of Economics and Accounting, 2025)
The objectives of this research were to create a web-based computerized system, fund internet installation costs, conduct outreach and analyze the contribution of the school information system to RA Al-Hida's progress, improve the quality of education for each student, and increase global prosperity by improving the standard of living for teachers and staff. Data collection methods include observation, interviews, and surveys. The methods used in developing this system include system development and implementation, as well as system testing and use. The trial implementation of this system was carried out for 10 days. The test reliability of the system, a survey was conducted using Google Forms with 4 questions and the rating scale of 1-5. The subjects were teachers and parents, consisting of 3 teachers and 3 parents. The results of this study are the creation of an integrated and comprehensive school management information system and learning management system that can improve the quality of education for students, teachers and parents understand the use of the system, and improve the standard of living for teachers and staff, thereby creating global prosperity.